Strategy for Strengthening Pharmacy Services in Primary Health Centers in Indonesia - Nanang Yunarto; Ida Diana Sari; Novi Sulistyaningrum; Siti Arda Mauliti; Herni Asih Setyorini; Nyoman Fitri; Arifayu Addiena Kurniatri; Esde Dianusana Etieka (Jurnal Kefarmasian Indonesia, 2026)
Implementation of pharmaceutical service standards in Indonesian primary health centers remains suboptimal despite recent regulatory mandates Government Regulation No. 28/2024 and Ministry of Health Regulation No. 26/2020, with persistent gaps in workforce distribution, clinical competency, facility infrastructure, supervision, and drug management systems. This study aimed to identify root causes of low implementation and to develop prioritized, operational strategies for strengthening pharmacy services in primary health centers across Indonesia. We conducted focus group discussions and direct field observations using the Minister of Health technical guidelines as the assessment framework; participants included provincial and district health office representatives, heads of community health centers, pharmacists, and pharmaceutical technicians across 20 primary health centers in ten provinces representing Indonesia. Findings reveal five interrelated barriers: chronic shortage and maldistribution of pharmacists and vocational pharmacy staff, with >50% of district-level centers lacking pharmacists; inadequate clinical pharmacy competencies and limited continuing professional development, restricting delivery of PIO, counseling, MESO, home pharmacy care, and visit services; insufficient pharmacy infrastructure and equipment (small, combined warehouse-workspaces, lack of dedicated counseling rooms, refrigeration, and monitoring devices); weak, irregular guidance and supervision at district/city level compounded by absent sanction mechanisms; and fragmented, time-consuming e-purchasing and multiple reporting systems that divert pharmacist time from clinical care. The study recommends a prioritized, integrated policy package clear implementing regulations with routine standardized supervision and sanctions, affirmative HR recruitment and incentive schemes, staged infrastructure upgrades, blended certified competency training with clinical mentoring, and integration/simplification of drug management/reporting system to enhance service quality, ensure medicine availability, and safeguard patient safety in primary care.